ANALISIS KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA CV GENCAR LAKSANA MANDIRI - Fida Arumingtyas; Tekni Megaster; Asriani Susiati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine the effect of compensation and competency on employee performance either partially or simultaneously at CV Gencar Laksana Mandiri. This study uses an descriptive method with a quantitative approach. Sampling was 38 people. Data processing was assisted by SPSS software version 25. If it is projected based on multiple regression tests it shows that the higher the value of compensation (X1) and competency (X2) simultaneously at a certain value, then the performance value (Y) increases at certain value too. Simultaneously compensation and competence have a significant effect on employee performance at CV.Gencar Laksana Mandiri. Partially, compensation has a positive and significant effect on employee performance, while competence also has a positive and significant effect on employee performance at CV.Gencar Laksana Mandiri.